PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PUZZLE CARD PADA MATERI BANGUN DATAR UNTUK PESERTA DIDIK KELAS IV SEKOLAH DASAR - Tania; Sofwan; Eka Sastrawari (LPPM Universitas Cipta Mandiri, 2024)
Puzzles are a form of game that challenges children's creativity and memory more deeply because they create motivation to always try to solve problems, but are still fun because they are done repeatedly. Puzzle learning media can be used in mathematics learning at school. Mathematics is a mandatory subject taught at school level. The aim of learning mathematics is not only so that students are able to solve routine mathematics problems (daily test questions, semester exams, national exams, or entrance exams to higher levels). This research aims to develop puzzle card media in flat shape material for class IV elementary school students, the validity of puzzle card media in flat shape material for class IV elementary school students, and the practicality of puzzle card media in flat shape material for class IV students elementary school. The approach in this research uses R&D (Research and Development) research and the model used in developing this puzzle card is the ADDIE (Analyze, Design, Develop, Evaluate) development model. The results of this research found that the process of developing Puzzle Card-based learning media on Flat Build material for Class IV Elementary School students was carried out based on the ADDIE development model with appropriate stages. The validity of the Puzzle Card media from the results of feasibility tests by material experts and media experts was declared suitable for use and testing. The practicality of the Puzzle Card media was tested on a large group and obtained a score of 1,341 categorized as